2019
DOI: 10.3390/jcm8040447
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in Serum Chloride and Acute Kidney Injury among Critically Ill Patients: A Retrospective Association Study

Abstract: Exposure to dyschloremia among critically ill patients is associated with an increased risk of acute kidney injury (AKI). We aimed to investigate how fluctuations in serum chloride (Cl−) are associated with the development of AKI in critically ill patients. We retrospectively analyzed medical records of adult patients admitted to the intensive care unit (ICU) between January 2012 and December 2017. Positive and negative fluctuations in Cl− were defined as the difference between the baseline Cl- and maximum Cl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…The authors also found that the AKI stages 1, 2, and 3 were all associated with a mean change in serum chloride level greater than or equal to 5 mEq/L. Similar relations were observed in other studies too (34,35). In the present study, the difference in chloride volume was clinically relevant and to the tune of 30-10 mEq/L in the first 2 days.…”
Section: Discussionsupporting
confidence: 91%
“…The authors also found that the AKI stages 1, 2, and 3 were all associated with a mean change in serum chloride level greater than or equal to 5 mEq/L. Similar relations were observed in other studies too (34,35). In the present study, the difference in chloride volume was clinically relevant and to the tune of 30-10 mEq/L in the first 2 days.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to the tubuloglomerular feedback mechanism, hyperchloremia can indirectly cause renal vasoconstriction by increasing the thromboxane release and renal vascular responsiveness to vasoconstrictors (e.g., angiotensin II) [ 9 , 24 ]. These pathophysiological mechanisms may play a role in the observed increased risk of acute kidney injury with hyperchloremia [ 5 , 14 , 23 , 25 ]. Hyperchloremic metabolic acidosis may be another possible pathophysiologic mechanism that leads to worse patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, hypochloremic patients had higher mortality and longer length of hospital stay compared to those without hypochloremia. In a different study, Oh et al examined temporal change of serum chloride levels in a heterogeneous ICU population and found that decrements in chloride levels by 1 mmol/L within 72 h of ICU stay were associated with a 4% increased odds of developing AKI at the same timepoint (21). This observation was also consistent in a subgroup of patients in which decrements in chloride levels were associated with increased levels of cystatin C, a marker of kidney dysfunction.…”
mentioning
confidence: 84%